Retro‐Friedel‐Crafts type cleavage of cyclic indolyl α‐amino esters. (9th June 2016) - Cao, Xiaoji; Wang, Ye; Mo, Yawen; Wu, Liang; Mo, Weimin
Abstract : Rationale: Chiral cyclic indolyl α‐amino esters are valuable substructures of peptides and peptidomimetics. Systematically exploring the fragmentation behavior of the protonated cyclic indolyl α‐amino esters by a combination of high‐resolution high‐energy collisional dissociation mass spectrometry, hydrogen‐deuterium exchange experiments and density functional theory (DFT) calculations is useful for further understanding their intrinsic properties and the fragmentation mechanisms of peptidomimetics constructed with them. Methods: All high‐resolution high‐energy collisional dissociation tandem mass spectrometry experiments were carried out using electrospray ionization hybrid Quadrupole‐Orbitrap mass spectrometry in positive ion mode. Only the labile hydrogens were exchanged with deuterium in hydrogen‐deuterium exchange experiments. Theoretical calculations were carried out by the DFT method at the B3LYP level with the 6‐311G(d, p) basis set in the Gaussian 03 package of programs. Results: In the fragmentation of protonated cyclic indolyl α‐amino esters, when the two labile hydrogens on the N 8 position are successively transferred to the C 3 and C 4 positions, a Friedel‐Crafts dealkylation reaction takes place spontaneously, with concomitant formation of an ion‐neutral complex of [cyclic N ‐sulfonyl ketimino esters/protonated indoles]. Direct separation of this complex formed the protonated indoles, while a stereoselective proton transfer between the two components in the complex gave rise to protonated cyclic N ‐sulfonyl ketimino esters, which coincided with the hydrogen‐deuterium experiments. Conclusions: Using H/D exchange experiments combined with theoretical calculations, a Friedel‐Crafts dealkylation reaction mediated by a stereoselective proton transfer in the [cyclic N ‐sulfonyl ketimino esters/protonated indoles] complex was proposed for the fragmentation of protonated cyclic indolyl α‐amino esters in high‐energy collisional dissociation tandem mass spectrometry for the first time. Copyright © 2016 John Wiley & Sons, Ltd.